KARAKTERISTIK IBU HAMIL DENGAN PENGETAHUAN DAN SIKAP DALAM MENGENAL TANDA BAHAYA KEHAMILAN - Ade Kurniawati; Dewi Nurdianti (LPPM Universitas Muhammadiyah Tasikmalaya, 2019)
The danger signs of pregnancy must be detected early because they can cause complications during pregnancy, labor and the puerperium. Lack of maternal knowledge about the danger signs of pregnancy will also affect the mother's attitude in responding to signs and dangers during pregnancy, childbirth and childbirth. This study aims to determine the relationship of characteristics of pregnant women with knowledge and attitudes in recognizing the danger signs of pregnancy. Methods: the method used is cross sectional. The sampling technique uses simple random sampling, with a calculation of the sample size obtained by 32 pregnant women. Results: the characteristics of pregnant women were mostly in the 20-34 year age group, which was 81.3%. Based on the level of research education most of them are tertiary education which is 53.1%. Characteristics of respondents based on parity 62.5% of respondents have more than one child. Based on work, most pregnant women work at 62.5%. Conclusion: The results of the analysis using Chi Square there is a relationship between the characteristics of pregnant women (age, education, work and parity) with the knowledge and attitudes of pregnant women in recognizing pregnancy danger signs with the value of p value for each variable smaller than alpha (?=0,05).